2005
DOI: 10.1590/s0101-20612005000100010
|View full text |Cite
|
Sign up to set email alerts
|

Folhas de alface lisa (Lactuca sativa) minimamente processadas armazenadas em atmosfera modificada: análises físicas, químicas e físico-químicas

Abstract: Há uma tendência para o uso de alimentos cada vez mais naturais, valorizando o sabor original dos produtos, onde o consumidor prima pela qualidade, principalmente às relacionadas com o valor nutritivo, as condições higiênico-sanitárias e as características sensoriais, portanto novas tecnologias estão sendo desenvolvidas no processamento de alimentos [10]. Na década de 70 surgiram nos EUA vegetais pré-processados, reunindo a praticidade e a conveniência. Esse mercado se expandiu e continua crescendo em todo mun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
11

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 8 publications
1
8
0
11
Order By: Relevance
“…These results differ with those of Delaquis et al (2000), who reported that the intensity of the taste of the lettuce decreases during storage. The taste of fresh lettuce has as main components sweetness and bitterness, and depends on the content and the combination of carbohydrates (sugars), organic acids, lipids and phenolic compounds (Mello et al, 2003;Menezes et al 2005). It is possible that storage at low temperature (5 °C) helped to reduce the rhythm of hydrolysis of sugars and…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results differ with those of Delaquis et al (2000), who reported that the intensity of the taste of the lettuce decreases during storage. The taste of fresh lettuce has as main components sweetness and bitterness, and depends on the content and the combination of carbohydrates (sugars), organic acids, lipids and phenolic compounds (Mello et al, 2003;Menezes et al 2005). It is possible that storage at low temperature (5 °C) helped to reduce the rhythm of hydrolysis of sugars and…”
Section: Resultsmentioning
confidence: 99%
“…Estos resultados difieren con Delaquis et al (2000), quienes reportan que la intensidad del sabor de la lechuga fresca disminuye durante el almacenamiento. El sabor de la lechuga fresca tiene como principales componentes al dulzor y el amargor, y es dependiente del contenido y combinación de carbohidratos (azúcares), ácidos orgánicos, lípidos y compuestos fenólicos (Mello et al, 2003;Menezes et al, 2005). Es posible que el almacenamiento a baja temperatura (5 °C) haya ayudado a reducir el ritmo de hidrólisis de azucares y otros componentes de la lechuga durante las etapas poscosecha, y esto pudo haber minimizado los cambios de sabor de este producto durante el periodo de almacenamiento.…”
Section: Resultados Y Discusiónunclassified
See 1 more Smart Citation
“…Ceres, Viçosa, v. 58, n.5, p. 638-644, set/out, 2011 trada uma pequena incidência de insetos (pulgão e lagarta) nas alfaces produzidas sob malhas termorefletoras 40%, avaliadas no dia da colheita. Menezes et al (2005) relataram que a deterioração de alface é evidenciada pela perda de cor, manchas, escurecimento das bordas e perda de turgidez.…”
Section: Resultsunclassified
“…Para melhor atender a essas exigências, vários estudos têm sido realizados 4,14,16,20,[24][25][26]28 , sendo que alguns deles têm proposto a irradiação como opção para promover a extensão da vida útil de produtos minimamente processados 3,10,17,19 .…”
Section: Introductionunclassified